Proceedings of the International Workshop on Semantic Big Data 2016
DOI: 10.1145/2928294.2928302
|View full text |Cite
|
Sign up to set email alerts
|

Semantic question answering on big data

Abstract: This article describes a high-precision semantic question answering (SQA) engine for large datasets. We employ an RDF store to index the semantic information extracted from large document collections and a natural language to SPARQL conversion module to find desired information. In order to be able to find answers to complex questions in structured/unstructured data resources, our system produces rich semantic structures from the data resources and then transforms the extracted knowledge into an RDF representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Keeping all components of the system up to date, particularly the ontology and the mapping, is still the responsibility of the administrators of the system and is performed manually. Tatu et al (2016) presented an approach for converting users natural language questions into SPARQL for querying and retrieving answers from an RDF store. Because the focus of their research is in transforming semantic structures identified in unstructured data sources (documents) to an RDF store that is accessible via natural language questions, the mapping of ontological concepts to (external) data sources is beyond the scope of their proposed framework.…”
Section: Ontology-based Applicationsmentioning
confidence: 99%
“…Keeping all components of the system up to date, particularly the ontology and the mapping, is still the responsibility of the administrators of the system and is performed manually. Tatu et al (2016) presented an approach for converting users natural language questions into SPARQL for querying and retrieving answers from an RDF store. Because the focus of their research is in transforming semantic structures identified in unstructured data sources (documents) to an RDF store that is accessible via natural language questions, the mapping of ontological concepts to (external) data sources is beyond the scope of their proposed framework.…”
Section: Ontology-based Applicationsmentioning
confidence: 99%